2009
DOI: 10.4018/jgcms.2009040101
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Law of Demand in a Virtual World

Abstract: We report results of an experiment on prices and demand in a fantasy-based virtual world. A virtual world is a persistent, synthetic, online environment that can be accessed by many users at the same time. Because most virtual worlds are built around a fantasy theme, complete with magic, monsters, and treasure, there is considerable skepticism that human behavior in such environments is in any way “normal.” Our world, “Arden,” was designed to test whether players in a typical fantasy environment were economica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In her work on science learning among adolescents in a virtual world, Kafai has studied interactions and learning, with the occasional ability to have the world altered to test a principle (Kafai, 2008; Neulight, Kafai, Kao, Foley, & Galas, 2007). In one recent case, Castronova and colleagues implemented a treatment and control condition version of a single‐player game to test economic behavior (Castronova et al, 2008). These initial outcomes beg an obvious question: Are these behaviors “real?” And by real, we mean: Are these behaviors similar to what we would observe had they occurred in the flesh and blood offline world?…”
mentioning
confidence: 99%
“…In her work on science learning among adolescents in a virtual world, Kafai has studied interactions and learning, with the occasional ability to have the world altered to test a principle (Kafai, 2008; Neulight, Kafai, Kao, Foley, & Galas, 2007). In one recent case, Castronova and colleagues implemented a treatment and control condition version of a single‐player game to test economic behavior (Castronova et al, 2008). These initial outcomes beg an obvious question: Are these behaviors “real?” And by real, we mean: Are these behaviors similar to what we would observe had they occurred in the flesh and blood offline world?…”
mentioning
confidence: 99%
“…Hamari and Keronen [11] used the random effects model to study a platform and found that enjoyment and prolonged use of the platform were more important predictors for purchases in virtual worlds than in games. Castronova et al [12] found that fantasy gamers may well be economically normal. They studied the consumption behavior of game players from the field of economics.…”
Section: Research Theorymentioning
confidence: 99%
“…However, the discussion can be generalized to firms selling goods and services online and those that monetize other scalable digital products and services such as video streaming, social media platforms, online learning delivery systems, and business analytics software. To date, with the exception of Castronova et al [7], who experimentally estimated the demand elasticity of digital items in an online game and reported that the price elasticity of the demand was −0.431, research in this field remains scarce.…”
Section: Introductionmentioning
confidence: 99%